Sinergisitas Penegakan Hukum Pada Kasus Pertambangan Emas Tanpa Izin di Kabupaten Banyumas, Jawa Tengah - Eni Muryani (BESTUUR, 2019)
Traditional unlicensed gold mining is found in various places in Indonesia. Mining is carried out by the people and processing gold using mercury, solely to make ends meet, they do not think the impact on environmental damage and pollution and legal aspects that can ensnare it. The purpose of this paper is to evaluate the synergy of the legal umbrella and law enforcement practices in unlicensed gold mining (PETI), especially in the case of gold mining in Banyumas Regency, Central Java Province. The research method used is juridical-normative. The research data used are primary and secondary legal materials. The results showed that gold mining carried out without permission in Banyumas District was prone to cause pollution to the environment and workplace accidents. The rise of unlicensed gold mining makes it difficult for government supervision. All existing regulations and laws in synergy regulate how the people's gold mining activities should not create problems for the environment. It's just that implementation in the field is still a lot of violations, especially licensing issues. Law enforcement against illegal gold mining is carried out with preventive and repressive measures. Keywords: Banyumas, Law Enforcement, Gold Mining.